BİTLİS YÖRESİ POMZASININ KENDİLİĞİNDEN YERLEŞEN HARÇLARDA MİNERAL KATKI OLARAK KULLANILABİLİRLİĞİ - ERGİN, ABDURRAHMAN (Fırat Üniveristesi, 2016)
Mineral katkı olarak Bitlis yöresi pomzası kullanılarak üretilen KYH' ların mekanik ve durabilite özelliklerini inceleyerek Türkiye rezervinin büyük bir bölümünü oluşturan Bitlis yöresi pomzasının kullanılma oranını artırmak hedeflenmektedir. Yürütülen deneylerle, öğütülmüş pomza ikameli kendiliğinden yerleşen harçların karışım oranları mini çökme-yayılma deneyleriyle belirlenmiştir. Daha sonra mineral katkı olarak öğütülmüş pomza tozu (ÖPT) ile üretilen kendiliğinden yerleşen harç (KYH) numuneleri hazırlanmış ve %5, %10, %15, %20, %25, %30, %35 ÖPT ilaveli karışımlar olmak üzere kontrol harcıyla birlikte 8 seri harç numuneleri üretilmiştir. Toplam 72 adet 40x40x160 mm3 harç numuneleri hazırlanmış ve 3 günlük, 28 günlük, 90 günlük kür sürelerinde şehir şebeke suyunda bekletilmiş, akabinde eğilmede çekme dayanımları ve basınç dayanımları ayrı ayrı ölçülmüştür. En yüksek dayanımların, %15 oranında ÖPT ilaveli karışımlarda olduğu tespit edilmiştir. Bununla birlikte 50x50x50 mm3 harç numuneleri de aynı ÖPT ilaveli karışım oranlarında toplam 24 adet hazırlanmış ve 28 günlük kür süresinde şehir şebeke suyunda bekletilmiş ve su emme deneyi uygulanmıştır. Çalışma sonucunda 28 günlük küre maruz harçlarda en düşük su emme oranına %10 ÖPT içeren harç numunesinin sahip olduğu belirlenmiştir. Farklı kür sürelerindeki eğilmede çekme dayanımları ve basınç dayanımları değerleri ile su emme oranı değerlerinin sonuçları arasında benzerlik olduğu görülmüştür.

This study aims to increase the potential use of the pumice found around Bitlis region, which makes up a large portion of Turkey's pumice reserves, through examining the mechanical and durability properties of SCMs, which are produced as mineral additives by use of the Bitlis region pumice. In the conducted experiments, the mixture proportions of self-compacting mortars substituted with the ground pumice were determined by mini-slump flow tests. Afterwards, the samples of the Self-Compacting Mortar (SCM), which are produced by the Ground Pumice Powder (GPP) as mineral additives, were prepared; and eight series of mortar samples with the SCM additive mixtures at rates of 5%, 10%, 15%, 20%, 25%, 30%, 35% together with control mortar were prepared. In total, 72 mortar samples with 40x40x160 mm3 dimensions were prepared and they were left in the city's tap water at curing periods of 3 days, 28 days and 90 days, respectively; soon after their flexural strengths and compressive strengths were measured separately. The nearest strengths to the control sample were found in the SCM additive mixtures at rate of 15%. In addition, 24 mortar cube samples at rates of the SCM additive mixtures with 50x50x50 mm3 dimensions were prepared, they were left in the city's tap water at curing periods of 28 days, and water absorption test was conducted. At the end of the study, the mortar samples including the SCM at rate of 10% seemed to have the lowest water absorption rate, among the mortars, which were left in the city's tap water at curing periods of 28 days. It was seen that there were parallels in the results between flexural strengths at different curing periods and compressive strength values and the water absorption rate values.
The potential use of a self-compacting mortars of pumice of bitlis region as mineral additives
Keywords: İnşaat Mühendisliği